Caracterizacion fisica y quimicq de granos de cacao fermentados, secos y tostados de la region de Chuao - Perez, E.=700 1 Alvarez, C.; Lares, M.
(Es, En)
ilus., 19 ref.
Keywords: THEOBROMA CACAO; ACIDEZ; PROPIEDADES FISICO-QUIMICAS; ACIDOS GRASOS; PROTEINAS; FIBRAS; VENEZUELA; PROTEINA CRUDA; CACAO